Una propuesta pragmatista para la unificación metodológica de la ciencia - Orozco Contreras, Richard (2011)
In this article, the author shows an aspect of Dewey's understanding shown towards science, specifically its unique method claim. While at first this methodological monism was represented by the action of 'thinking', later was conceptualized with the word 'investigate'. In the first section, the author interprets the first identification of thinking and the only method, then, in a second section to show what Dewey means to investigate the method. In a third section the author faces the positive impact on science taking a unique approach by addressing the confrontational positions proposed different methods to maintain the natural sciences and the sciences.